2004
DOI: 10.1002/cb.163
|View full text |Cite
|
Sign up to set email alerts
|

Influences on the perceived risk of purchasing online

Abstract: This paper examines whether the perceived risk of online purchasing by consumers varies with the frequency of previous purchases, satisfaction with previous purchase experiences, the good/service orientation of an intended purchase and the level of purchase decision involvement required. No association was found between the frequency of online purchasing and perceived risk, although satisfaction with prior internet purchases was negatively associated with the perceived risk of intended purchases, but only for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
161
0
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(194 citation statements)
references
References 33 publications
7
161
0
11
Order By: Relevance
“…7, No. 1; For instance, Pires et al (2004) found no significant relationship between previous online shopping experience and perceived risk among Australian internet users. A possible explanation for this is that Australian online shopping facilities and infrastructure differ significantly from those provided in Jordan.…”
Section: Group Comparisonmentioning
confidence: 91%
See 1 more Smart Citation
“…7, No. 1; For instance, Pires et al (2004) found no significant relationship between previous online shopping experience and perceived risk among Australian internet users. A possible explanation for this is that Australian online shopping facilities and infrastructure differ significantly from those provided in Jordan.…”
Section: Group Comparisonmentioning
confidence: 91%
“…Perceived risk has thus been implicitly and explicitly incorporated into the extant online adoption and acceptance literature, and found to be a significant determinant of the adoption of new technologies (Zhang et al, 2012;2008;Dimitrova & Chen, 2006). However, risk perception is frequently overlooked or given less detailed attention than other variables; for instance, much of the current literature on the adoption and acceptance of online shopping treats risk perception as a one-dimensional construct (Pires, Stanton, & Eckford, 2004) or sometimes as an external factor that affects intention through other factors such as trust and PEOU (e.g., Gefen, Pavlou, Warkentin, & Gregory, 2002;Horst, Kuttschreuter, & Gutteling, 2007;Featherman & Pavlou, 2003). There are nevertheless some researchers (e.g., Almousa, 2014;Dai et al, 2014;Zheng et al 2012) who have argued that risk perception should be treated as a multidimensional construct in order to gain a better understanding of its role in forming individuals' intention to adopt online shopping, and to identify the types of risks associated with this activity (Almousa, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While such methods are common within disciplines such as psychology, they have nevertheless been used previously to study the impact of consumer behavior generally (Martin & Marshall 1999) and to investigate risk in the online retail context in particular (Pires et al 2004;Tan 1999). …”
Section: Methodsmentioning
confidence: 99%
“…In this regard, Donthu and Garcia (1999) assert that risk aversion plays a critical role in this transition. Other research has highlighted that perceived risk in the online channel is mitigated by technological experience (Dillon & Reif 2004), frequency of use (Pires et al 2004), and the type and value of products purchased (Doolin et al 2005). Table 1 provides a summary of the key literature related to risk perceptions in the online environment.…”
Section: Background Theorymentioning
confidence: 99%
“…Assim, os resultados deste estudo indicaram que a utilização de apaziguadores visando reduzir, ou mesmo anular a percepção de riscos, não sofreu alteração significativa entre os grupos investigados. Essas conclusões corroboram com os achados de outros autores, como Pires et al (2004), que também avaliaram as possíveis relações entre experiência de compra e os riscos percebidos, sem que seus achados apontassem para uma possível influência dos grupos sobre as variáveis.…”
Section: Variável Estratégia De Redução Dos Riscos Percebidosunclassified